2007
DOI: 10.1002/cncr.22570
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplastic syndromes

Abstract: BACKGROUND. Myelodysplastic syndromes (MDS) became reportable to the Surveillance, Epidemiology, and End Results (SEER) Program (the United States cancer surveillance program) in 2001. This provided the first opportunity to examine the incidence and survival of patients with MDS in the United States using a large, population‐based database. METHODS. The SEER 17 regions public‐use database (November 2005 submission) was accessed to obtain data on the frequency, incidence, and survival of patients with MDS. Geog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
127
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 478 publications
(138 citation statements)
references
References 11 publications
8
127
1
2
Order By: Relevance
“…Patients with MDS commonly require chronic red blood cell (RBC) transfusions which can lead to iron overload resulting in eventual damage to the liver, heart and pancreas, and there is an increased risk of cardiac events for transfused patients when compared with non-transfused patients [2]. A 2007 Surveillance, Epidemiology and End Results (SEER) report [3] estimated that over 10 000 new cases of MDS were diagnosed in the USA between 2001 and 2003, but other studies have reported higher incidence estimates based on Medicare claims [4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…Patients with MDS commonly require chronic red blood cell (RBC) transfusions which can lead to iron overload resulting in eventual damage to the liver, heart and pancreas, and there is an increased risk of cardiac events for transfused patients when compared with non-transfused patients [2]. A 2007 Surveillance, Epidemiology and End Results (SEER) report [3] estimated that over 10 000 new cases of MDS were diagnosed in the USA between 2001 and 2003, but other studies have reported higher incidence estimates based on Medicare claims [4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…Although decitabine 20 mg/m 2 /day for 5 days has achieved great success in the treatment of MDS with a remarkably high complete response rate (32-39%) [2,5,6], the main reasons for early discontinuation of decitabine, other than treatment failure, were severe infection and hemorrhage due to BM suppression, especially for particularly weak or elderly patients. On the other hand, in China, many patients give up therapy because of the economic burden, even among responders.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of MDS increases markedly with age, with approximately 86% of patients diagnosed over the age of 60 years (the median age is 76 years) [2]. The only curative therapy for MDS is allogeneic stem cell transplantation, which is usually not applicable to elderly patients because of their poorer physical condition.…”
Section: Introductionmentioning
confidence: 99%
“…A heterozygous mutation of the hematopoietic transcription factor RUNX1, regulating large parts of MK development and maturation, results in familial platelet disorder (FPD), a disease characterized by a deficiency in platelet formation [138][139][140]. During lifetime, patients develop an increasing risk of attaining AML or MDS (20-60%), which is commonly associated with a poor prognosis [141,142]. Combining an excisable lentiviral polycistron encoding for OCT4, SOX2, KLF4, and cMYC and a small molecule-assisted approach, we could recently derive iPSCs from a patient suffering from congenital FPD, which will be employed as model for FPD and secondary leukemic aberrations [48].…”
Section: Platelet Disordersmentioning
confidence: 99%